(untitled) (Per Musi, 2021)
Public participation in art performances has been leveraged by the use of technology as a mediating element between the public and artists. However, technological mediation alone may not be enough to ensure effective auditory participation. In this article, we present the performance “ O Chaos das 5 ”, an audiovisual digital performance with a strong technological support that had the support of game theory to achieve a more effective participation of the audience in their presentations.